2009
DOI: 10.1088/0253-6102/51/5/21
|View full text |Cite
|
Sign up to set email alerts
|

Study on Duality of Wave and Particle of Turbulence Using CML Models

Abstract: A family of coupled map lattice (CML) models has been developed to simulate the evolutional mechanism of interactions of convection, diffusion, and dispersion in both weakly and strongly coupled cases. Not only coherent and turbulent properties as well as their relations, but also the transitional states between convection dominating, diffusion dominating and dispersion dominating are analyzed to demonstrate the essential characteristics of any state. Numerical results show that the models are capable of simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…These investigations stimulate us to explore the quantum-classical transition in condition that the classical motion is almost unaffected. In this paper, we make further investigation on the quantum-classical transition for the models analyzed in [16]. Our results show that the quantum-classical transition persists by decreasing the mass of the second KR, and at the same time, decreasing the effective Planck's constant and the interaction strength proportionally.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…These investigations stimulate us to explore the quantum-classical transition in condition that the classical motion is almost unaffected. In this paper, we make further investigation on the quantum-classical transition for the models analyzed in [16]. Our results show that the quantum-classical transition persists by decreasing the mass of the second KR, and at the same time, decreasing the effective Planck's constant and the interaction strength proportionally.…”
mentioning
confidence: 80%
“…The system analyzed in [15] consists of two particles with very different masses, in which the particle of very small mass possesses little energy to affect the classical motion of the other one of larger mass. In a recent paper, [16] we showed that the coupling with a particle of very small mass can destroy dynamical localization of KR. The quantum-classical transition happens as the coupling strength increases.…”
mentioning
confidence: 97%